2022
DOI: 10.3390/ijerph19105944
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Trauma: The Mediating Effects of Family Health

Abstract: Family health is important to the well-being of individual family members and the collective family unit, and as such, may serve as a mediator for the intergenerational transmission of trauma (ITT). This study aimed to understand the intergenerational impact of parent’s adverse and positive childhood experiences (ACEs and PCEs) on their children’s adverse family experiences (AFEs) and how family health mediated those relationships. The sample consisted of 482 heterosexual married or cohabiting couples (dyads) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Another explanation may include that as the data were collected during the COVID-19 pandemic, the import of earlier traumatic experiences became greater in a stressful time. In such cases, current positive experiences such as PAEs or healthy households were more important than prior positive experiences (38,39). In models where PCEs were associated with higher odds for depression, this is likely explained by the strong correlation between PCEs and PAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may include that as the data were collected during the COVID-19 pandemic, the import of earlier traumatic experiences became greater in a stressful time. In such cases, current positive experiences such as PAEs or healthy households were more important than prior positive experiences (38,39). In models where PCEs were associated with higher odds for depression, this is likely explained by the strong correlation between PCEs and PAEs.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in behavior can include an increased risk for the experience of new adversities and trauma, a pattern also observed in individuals at familial risk for mood disorders with a risk of intergenerational transmission of trauma. 84 Individuals who have experienced childhood maltreatment may further have difficulties forming healthy relationships, experiencing pleasure, or regulating their emotions, even years after the trauma has occurred, leading to a vicious cycle where adverse childhood experiences trigger health-harming behavior in young adulthood. 85,86 For example, individuals who have experienced more childhood maltreatment more often drink and smoke, 87 habits that can also induce epigenetic changes.…”
Section: Hen and Eggmentioning
confidence: 99%
“…Almost all study samples were restricted to individuals 18 years and older except two studies that included pregnant individuals as young as 14 to 16 years (Chung et al, 2008;Anderson, 2021) and another study that included college or university students as young as 17 years (Hou et al, 2022). Three studies also examined parent-reported outcomes of children in the next generation (Reese et al, 2022;Johnson et al, 2022;Zhu et al, 2023).…”
Section: Descriptive Informationmentioning
confidence: 99%
“…Higher PCEs consistently predicted more positive psychosocial functioning and lower psychosocial stress, even after accounting for childhood adversity. Specifically, higher PCEs significantly predicted less loneliness (Doom et al, 2021;; less shame (Novilla et al, 2022;Rollins & Crandall, 2021); lower affective lability (Almeida et al, 2023); less aggressive behavior (Narayan et al, 2023a); more positive body image ; higher locus of control, forgiveness, gratitude, and familial closeness (Crandall et al, 2019); greater family health (Daines et al, 2021;Reese et al, 2022); higher social support (Bethell et al, 2019;Daines et al, 2021); higher thriving (Hanson et al, 2022) and flourishing (Yu et al, 2022); better self-regulation (Hanson et al, 2022;Rollins & Crandall, 2021); greater wellbeing and mental toughness (Shaw et al, 2022); greater life satisfaction and meaning ; more prosocial behaviors (Zhan et al, 2021); more elaborate positive memories with childhood caregivers ; more secure and less ambivalent attachment styles (Anderson, 2021); and higher self-compassion (Chasson & Taubman-Ben-Ari, 2022). Zhu et al (2023) also found that higher parental PCEs predicted lower difficulties and prosocial problems in their children.…”
Section: Mental Health Outcomesmentioning
confidence: 99%